Distribution and characterization of Clostridium difficile isolated from dogs in Japan. (February 2016) - Usui, Masaru; Suzuki, Kaname; Oka, Kentaro; Miyamoto, Kentaro; Takahashi, Motomichi; Inamatsu, Takashi; Kamiya, Shigeru; Tamura, Yutaka
Abstract: We collected 204 nondiarrhoeic canine fecal samples and isolated 68 Clostridium difficile strains from 62 of these samples. Strains were grouped into 29 PCR ribotypes. Only 47% of the strains were toxigenic. Highlights: We report that a survey of fecal samples from dogs in Japan indicates that 30% of dogs harbor Clostridium difficile . Many isolates obtained from these dogs are toxigenic, and some are resistant to antimicrobials.